THE EFFECT OF FLOOR GYMNASTICS TRAINING ON THE BODY BALANCE OF GRADE IX STUDENTS AT SMP NEGERI 2 BAMBEL - Irwandi; Melfa Br Nababan; Orbit Irwansyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aimed to determine the effect of a structured, one-week floor gymnastics training program on the body balance of ninth-grade students. Employing a quantitative approach with a one-group pretest-posttest design, the research involved 30 students from SMP Negeri 2 Bambel who were physically healthy and aged between 13 and 15 years. The intervention consisted of floor gymnastics exercises conducted three times per week for one week, with each session lasting 60 minutes. Body balance was measured before and after the training using an instrument based on five floor gymnastics indicators (candle stance, one-legged stand, back arch, handstand, and straight-line walk), each scored on a scale of 1 to 3. The results indicated a significant improvement in balance scores following the intervention. The mean pretest score was 9.20, which increased to a mean posttest score of 13.26, with a mean difference of 4.06. The data were normally distributed, as confirmed by the Shapiro-Wilk test (p = 0.240 > 0.05). A paired sample t-test revealed a statistically significant difference between the pretest and posttest scores (t = 22.68, p < 0.001). These findings conclusively demonstrate that a short-term, intensive program of floor gymnastics training is effective in significantly improving both static and dynamic body balance in adolescents. This supports the integration of structured gymnastics into school physical education curricula to enhance students' fundamental motor skills.